1962
DOI: 10.1126/science.136.3516.653
|View full text |Cite
|
Sign up to set email alerts
|

New Biological Effect of the Gases of the Helium Group

Abstract: The mold Neurospora crassa ATCC 5297a was grown in gaseous environments of helium, neon, argon, krypton, xenon, or nitrogen containing approximately 5 percent oxygen. A close correlation of the growth rate R (in millimeters per hour at 30 degrees C) with the molecular weight MW of the chemically inert gas was observed. This correlation is described by the empirical equation: R = 3.88 - 0.1785 (MW).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The relationship between the physical properties of such gases and effects of their biological activity are recognised [7,20,21,22]. Based on the results of this study it appears that within the applied pressure range /up to 4 atm/, the narcotic effects and toxicity of the mixtures used were not revealed.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The relationship between the physical properties of such gases and effects of their biological activity are recognised [7,20,21,22]. Based on the results of this study it appears that within the applied pressure range /up to 4 atm/, the narcotic effects and toxicity of the mixtures used were not revealed.…”
Section: Discussionmentioning
confidence: 72%
“…The result obtained in the experiment of breathing with argon mixture is associated with disorders in the respiratory mechanics resulting from the high density of this mixture. In our study, the Ar/02 mixture at 4 atm was 6.61 times denser than air, and it appears that in a long-term physical activity it would lead to respiratory failure [5,7,21,22].…”
Section: Discussionmentioning
confidence: 93%
“…Increasing the ambient temperature (T a ) at 1 atm, and thus decreasing the driving force for heat loss, decreases the difference between V O 2 of rats in air and that in He [26]. Although there seems to be an effect on the metabolic rate, depending on the gas mixture used, that can be attributed to the thermal properties of the gas mixture, many reports of metabolic disturbances in tissue slices [29], insects [8], microorganisms [36], whole-animal studies in mammals [7,21,23], and inhibition of enzyme activity in vitro [35] have suggested other possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of helium or argon for the nitrogen in air at one atmosphere apparently has no effect on the growth and gas exchange of Chlorella pyrenoidosa (1). Experiments with Neuspora crassa grown in atmospheres of helium, neon, nitrogen, argon, krypton, and xenon showed an inverse relationship between growth rate of the organism and the square root of the molecular weight of the gas (6). Latterell (3) reported a significant decrease in germination when rye seeds were exposed to a helium atmosphere at 760 mm of Hg.…”
mentioning
confidence: 99%